Bellegard and Mariadahl, Pottawatomie County - Doll, Alexander; Manbeck, Mark (Kansas State University, The Chapman Center for Rural Studies, 2012)
Against all hopes, Bellegard, the Swedish farming oasis, never truly became a town. But in symbiosis with Mariadahl, both “towns” persisted for approximately 30 years before Bellegard dissolved. Their union was the only thing that kept either town alive. Bellegard was home to the famous “cutting edge security” post office and a school. From a single scrap of evidence, our two man investigative force pieced together a riveting story of this one town with two faces, which we know as Bellegard and Mariadahl.
Alexander Doll and Mark Manbeck , “Bellegard and Mariadahl, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/107.
Keywords: Bellegard; Mariadahl; Swedish; Tuttle Creek Dam; C.J. Holt; James P. Shannon